Pengukuran Waktu Kerja Dengan Metode Time Motion Study Untuk Meningkatkan Produktivitas Kerja Produksi Greenware (Studi kasus : PT XYZ) - Fardiansyah, Ismail; Widodo, Tri; Anggraini, Weli (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2022)
This study aims to determine the working time in order to increase productivity in greenware production in the formation section, the productivity of workers that will be calculated in this final project is the productivity of workers in the formation section in greenware production because the results of the production process every day are different and still exist,which has not reached its production target. The calculation of productivity is carried out using the time and study method, after obtaining the working time used to carry out the production process, then a new work method is applied to increase productivity results and a comparison is made before and after the implementation of the new work method, After applying the time motion study method to production Greenware in the formation section is known for the productivity results obtained, which are 121,350. After measuring working time using a time study and implementing the proposed improvement, the productivity results increased for the initial productivity results from 121.350 to 134.100, or an increase of 10.5%. Keywords: Working Time, Productivity,production targets, time and study, standard time.